Administrative authority powers of the State treasury services: concept and types - Прекрасна, Олена Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article put forward and proved the hypothesis that the powers of the State Treasury Service of Ukraine are administrative enforcement nature. An analysis of foreign legislation proposed borrow experience and introduce in Ukrainian national legislation the term "coercive measures for violations of budget legislation." In this work have been classified administrative coercive powers of the State Treasury Service of Ukraine. For this purpose, the author used a correlation with the types of administrative coercion, as well as comparative legal analysis and administrative provisions of the budget legislation. Consequently, there are three types of administrative enforcement powers of the State Treasury Service of Ukraine and her officials: 1) preventive power rights and obligations aimed at prevention, to prevent violations in a budgetary sphere, prevention of negative consequences, protection of the public interest. Formulated a definition of the concept of preventive administrative enforcement powers of the State Treasury. This – regulated power state law rights and obligations implemented in the absence of of wrongful conduct on the part of the object of legal enforcement to prevent of possible violations and of negative consequences in a budgetary sphere; 2) power rights and obligations that are intended to taking measures to stop (interrupt) unlawful behavior, to prevent the onset (elimination) of harmful consequences of wrongful conduct, to ensure those responsible be brought to responsibility. 3) power rights and obligations on those responsible be brought to administrative responsibility. As part of these powers and allocated: a) the power to impose administrative sanctions; b) the power to compulsory execution administrative sanctions. Administrative enforcement powers of the State Treasury Service of Ukraine proposed to understand as established by the state to set that subjects and its officials, officials of government legal rights and obligations regarding the application of administrative coercion aimed at preventing and suppression of offenses and punishment for their commitment in the field of treasury services for budget. Also the author proposed some amendments to the Budget Code of Ukraine and the Code of Ukraine on Administrative Offences.